2008
DOI: 10.1292/jvms.70.603
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Change of Porcine Circovirus Type 2 on Japanese Pig Farms as Revealed by Restriction Fragment Length Polymorphism Analysis

Abstract: ABSTRACT. Porcine circovirus type 2 (PCV2) has been recognized as the causal agent of postweaning multisystemic wasting syndrome and can be divided into two major genotypic groups. We developed a method of restriction fragment length polymorphism (RFLP) analysis of PCV2 open reading frame 2 for easy discrimination between the two major groups. Genotyping of PCV2 isolates from 10 Japanese commercial pig farms was performed, and the analysis revealed that both PCV2 groups and at least five RFLP types of PCV2 are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…We previously reported a genotypic change from PCV2a to PCV2b on Japanese commercial pig farms [29]. Those farms were included in this study as farms infected with PCV2b.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously reported a genotypic change from PCV2a to PCV2b on Japanese commercial pig farms [29]. Those farms were included in this study as farms infected with PCV2b.…”
Section: Discussionmentioning
confidence: 99%
“…Sampling of sera was performed in same month (i. * The RFLP types were determined by the previously described method [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PCV2c genotype has only been found in Denmark to date [31]. In recent years, several reports have suggested that PCV2b is the predominant genotype in many countries worldwide, including Brazil [8,11], Canada [14,15] [16,32]. In Taiwan, the first PCV2 outbreak was confirmed in 2001 [3], and a high prevalence of PCV2 infection was noted thereafter.…”
mentioning
confidence: 99%